Homicide or Suicide: How Nudity Factors into This Determination - Craun, Sarah W. (Homicide studies, 2022)
Anecdotal reports of deceased celebrities being found nude abound, yet research is lacking regarding the frequency of nudity at death. Moreover, it is unknown if nudity at the time of death is a useful investigative clue or a distracting non-factor in equivocal death cases. This study used data from 119,145 homicides and suicides reported to the Centers for Disease Control to explore victim nudity, prior life stressors, and demographics on the likelihood of a death being a homicide or a suicide. Logistic regression results indicate that a female victim being found nude is a strong indicator of homicide.